Penurunan Kadar Malondialdehid Aorta Abdominal Tikus Hiperkolesterolemia yang Diinduksi Mentega Putih setelah Pemberian Probiotik: Penurunan Kadar Malondialdehid Aorta Abdominal Tikus Hiperkolesterolemia setelah Pemberian Probiotik - Dewanti, Alfi Brillianti Chrisna; Lusiantari, Rokhima; Pramaningtyas, Miranti Dewi (Universitas Airlangga, 2024)
Background: One of the risk factors for hypercholesterolemia is a high-fat diet. Hypercholesterolemia can cause an increase in free radicals in the body, one of which is malondialdehyde (MDA). Probiotics are food additives that have a positive effect on digestive health. The potential of probiotics as antihypercholesterolemia still requires further study. Objectives: To determine the effect of adding probiotics on MDA levels of the abdominal aorta in a hypercholesterolemic rat model. Methods: Nineteen male Wistar rats were divided into 5 groups: negative control (C-), positive control (C+), and three probiotic groups (T1, T2, and T3). The negative control group received standard food while the positive group received standard food and shortening. The probiotic group received standard feed and white butter, with probiotics at three different doses as treatment for 10 weeks. After termination, the abdominal aortic MDA levels were checked. Analysis of the data obtained used the Kruskal-Wallis test. Results: The mean levels of abdominal aortic MDA were 1.78 ± 0.11 nmol/g, 5.23 ± 0.51 nmol/g, 4.02 ± 0.02 nmol/g, 3.46 ± 0.16 nmol/g, and 2.20 ± 0.06 nmol/g for groups C-, C+, T1, T2, and T3, respectively. The statistical analysis showed that there was a significant difference in the abdominal aortic MDA levels (p<0.05). The T3 group showed the lowest abdominal aortic MDA levels of all. Conclusions: The administration of probiotics to male Wistar rats induced by shortening had a significant effect on the abdominal aortic MDA levels.